Media-driven polarization: Evidence from the US - Mickael Melki; Petros Sekeris (Economics: The Open-Access, Open-Assessment E-Journal, 2019)
The authors use US data on media coverage of politics and individual survey data to document that citizens exposed to more politicized newspapers have more extreme political preferences. This polarization effect of media is mainly driven by individuals who harbor liberal opinions reading more newspapers, as opposed to individuals endorsing rather conservative positions. More politicized media also reinforce other aspects of citizens' political sophistication such as political knowledge. This enhanced political sophistication materializes in observable involvement in politics, measured by campaign contributions.
http://dx.doi.org/10.7910/DVN/0IEOA8
Keywords: K4; H0; 330; media; ideological polarization; political sophistication